El estado del medio ambiente en las ciudades latinoamericanas - Dávila, Julio D. (El Colegio de México A.C., 1998)
The author describes the environment in Latin American cities, detailing the negative effects on the urban environment that result from the combination of an increasing demographic growth, the process of urbanization and the concentration of economic activities in some cities.Besides analyzing some serious water, soil and air problems, this work offers a general picture of the institutional changes that are taking place and that allow us to foresee, even in a context of poverty, some alternatives for facing environmental damage. According to the author, the basic changes needed to improve the environment in Latin America regard implementing educational programs to develop an authentic awareness and careful behavior towards the environment.